Lipid exchange and inflammatory markers in patients with coronary artery disease and atrial fibrillation - I. O. Melnychuk; M. L. Sharaieva; V. H. Lyzogub (Сучасні медичні технології, 2023)
Aim. To investigate lipid exchange violations, inflammatory markers levels, their connections in coronary artery disease (CAD) patients with atrial fibrillation (AF) and their role in AF paroxysm development and duration.